Results and Data Analysis - Jauhar, Junaimah; Abdul Ghani, Ahmad Bashawir; Islam, Rabiul (Springer, 2016)
In this chapter, the explanation on the analysis performed and the results obtained had been expounded.Based on the results, the conclusion of the hypotheses testing has been elucidated whereby six hypotheses were tested and all six were supported. Meanwhile, personality was found to have a moderating effect on brain drain.